Uma proposta de mudança organizacional das secretarias departamentais do Centro de Ciências Agrárias da Universidade Federal do Espírito Santo à luz do princípio constitucional da eficiência tendo como referência o modelo de excelência em gestão pública do Programa GESPÚBLICA - Marques, Fabiana Vidal Monteiro da Silva (2015)
This work aims to propose the organizational change of departmental secretaries of Agricultural Sciences Center of the Federal University of Espírito Santo in the light of the constitutional principle of efficiency with reference to the Model of Excellence in Public Management GESPÚBLICA Program. An exploratory study was conducted to survey the existing techniques and bibliographical information. Then we proceeded a survey, using a semi-structured questionnaire, with the participation of administrative staff crowded in the departments which perform the function of departmental secretaries, besides the application of a vertical flow chart in order to map, model, and standardize developed administrative routines and manage information, promoting standardization and registration of institutional knowledge, meeting the needs of your target audience efficiently and striving for excellence in public administration